Analytical Solution of Homogeneous One-Dimensional Heat Equation with Neumann Boundary Conditions - Subani N.; Jamaluddin F.; Mohamed M.A.H.; Badrolhisam A.D.H. (Institute of Physics Publishing, 2024)
Indexed by Scopus/ERA